Strategi Pemerintah Nagari Dalko dalam Pengemebangan Objek Wisata Saribu Sarasah di Nagari Dalko - Monika Rizaldi, Mutiara; Mubarak, Adil (Policy, Law and Political Research Center, 2024)
This study examines the strategies the Nagari Dalko Government implemented in developing the Saribu Sarasah tourist attraction. This study uses a qualitative approach with a descriptive method, and the research location is centred on the Office of the Wali Nagari Dalko, Agam Regency. Data were obtained through interviews, observation, and documentation. The results showed that the Dalko Nagari Government still needs to develop a concrete strategy for developing the Saribu Sarasah tourist attraction. Currently, the village government is working with KKN students from Padang State University (UNP) to create this tourist area sustainably in the future.